The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae) - Enghoff, Henrik; Reboleira, Ana Sofia (European Journal of Taxonomy, 2020)
The first eyeless species of the suborder Spirostreptidea, Odontostreptus fadriquei sp. nov., is described from a cave in Morocco. The new species, which exhibits some troglomorphic traits, is compared with the highly variable O. maroccanus (Attems, 1914) of which new material is presented.